Pengembangan Immersive Learning Berbasis Natural User Interface (NUI) Pada Materi Pembelajaran Tenis Meja - Yusro, Afif Rois; Ulfa, Saida; Kuswandi, Dedi (Universitas Negeri Malang, 2022)
Modern learning with Immersive learning comes with AR and VR concepts to improve students' psychomotor learning skills. Immersive Learning is structured with the concept of learning table tennis movements as a learning medium using sensors that can read human motion. This study aims to help students determine the level of objectivity in learning the basic movements of table tennis using the Lee & Owens development model. The research subjects used 10 students of class X SMKN 1 Pasirian. The results of the development that have been validated by several experts are categorized as very valid. While the test results of immersive learning applications are determined by looking at the results of individual trials with fairly valid results, and field tests with valid results. This shows that this interactive learning multimedia is quite effective in improving psychomotor learning outcomes. In addition, immersive learning media can be implemented as the main learning media in the learning process of basic table tennis movements. Abstrak Pembelajaran modern dengan Immersive learning hadir dengan konsep AR dan VR untuk meningkatkan keterampilan belajar psikomotor siswa. Immersive learning disusun dengan konsep pembelajaran gerakan tenis meja sebagai media pembelajaran menggunakan sensor yang dapat membaca gerak manusia. Penelitian ini bertujuan membantu peserta didik mengetahui tingkat objektivitas dalam mempelajari gerakan dasar tenis meja dengan model pengembangan Lee & Owens. Subjek penelitian menggunakan siswa kelas X SMKN 1 Pasirian sebanyak 10 siswa. Hasil pengembangan yang sudah divalidasi oleh ahli media dan ahli materi mendapat kategori sangat valid. Sedangkan hasil uji coba aplikasi immersive learning ditentukan dengan melihat hasil dari ujicoba perseorangan dengan hasil cukup valid, dan uji lapangan dengan hasil uji yang valid. Hasil ini menunjukan pembelajaran immersive learning tenis meja dinyatakan cukup efektif pada hasil belajarnya. Dengan demikian media pembelajaran immersive learing dapat diimplementasikan sebagai media pembelajaran utama pada proses pembelajaran gerakan dasar tenis meja.